2018
DOI: 10.1103/physrevmaterials.2.065401
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic study of the electronic contact resistivity between the half-Heusler alloys (HfCoSb, HfZrCoSb, HfZrNiSn) and the metal Ag

Abstract: Half-Heusler(HH) alloys have shown promising thermoelectric properties in the medium and high temperature range. To harness these material properties for thermoelectric applications, it is important to realize electrical contacts with low electrical contact resistivity. However, little is known about the detailed structural and electronic properties of such contacts, and the expected values of contact resistivity. Here, we employ atomistic ab initio calculations to study electrical contacts in a subclass of HH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…In particular we are interested in the fundamental limit of the electrical contact resistivity at these interfaces. To this end we employ a previously developed atomistic approach [17,18] that combines first-principles simulations with macroscopic modeling. The approach uses: i) ab initio calculations based on Density Functional Theory (DFT) [19] to obtain the electronic properties near the interface.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…In particular we are interested in the fundamental limit of the electrical contact resistivity at these interfaces. To this end we employ a previously developed atomistic approach [17,18] that combines first-principles simulations with macroscopic modeling. The approach uses: i) ab initio calculations based on Density Functional Theory (DFT) [19] to obtain the electronic properties near the interface.…”
mentioning
confidence: 99%
“…We begin by investigating from first-principles the basic properties of the HH and FH systems in bulk form. In a previous study [18] we calculated the low-temperature properties of Ag contacts to several HH alloys including compounds from the family (Zr,Hf)NiSn. In particular we found that bulk HH properties important for band alignment at the metal interface (such as the electron affinity or the band gap) do not depend significantly on the alloy composition or doping.…”
mentioning
confidence: 99%
See 3 more Smart Citations